Embodiment and legal theory : law in Fifty Shades of Grey - Duncanson, Kirsty (Abingdon, Oxon [UK] ; New York, NY : Routledge, 2025)
"This book addresses the importance of the body in legal theory, through an analysis of the film Fifty Shades of Grey. As physical beings, we experience law in sensations of outrage when it is applied unethically, righteousness when it finds justice, and joy when it establishes partnerships in marriage. Our bodies feel and know law. In Embodiment and Legal Theory, it is argued that our bodies also theorise law. It is proposed that our bodies are involved in comprehending, negotiating and reimagining the legal concepts that shape our lives. As a medium designed to engage us by stimulating our bodily reactions of tears, laughter, shock and titillation, cinema provides an ideal site for exploring how bodies participate in legal arguments and the construction of legal meaning. For this reason, through a deep analysis of the film Fifty Shades of Grey (2014), this book presents a theory of embodied jurisprudence. At the intersection of legal theory and film studies, this book will appeal to students and scholars in both these areas, as well as in criminology and cultural studies"--
Interlude -- Twilight delight reader agency as philosophy -- The Scene -- First Reading : The Frisson of Sexual Agency -- Second Reading : The Discomforts of Subordination -- Why Am I Crying? -- Third Reading 1 : Legal Sensations Between Orgasms -- Third Reading 2 : Doing Jurisprudence with Your Body -- Postlude -- Embodied Legal Philosophy Beyond the Cinema and Jurisprudential Sex.
Keywords: James, E. L; Law in motion pictures; Law -- Philosophy; Law in literature; Sex customs in literature; LAW / General; LAW / Criminal Law / General; LAW / Gender & the Law